„Sprawa realizmu w plastyce kształtującej”. Design i jego krytyka wobec realizmu socjalistycznego - Kal, Elżbieta (Załącznik Kulturoznawczy, 2019)
This text concerns itself with Polish design and its criticism in the period of socialist realism (1949/50–1955). The title refers to a terminological proposal by Janusz Bogucki who looked for new terms for his work in the new system. The division into ‘pure’ and ‘usable’ arts was considered as an anachronism in socialism in which all artistic fields were to fulfil social functions. As optimal, the critic considered a division of arts into the ‘imaging’ (painting, sculpture, and graphic) and ‘formative’ (shaping human surroundings and public space – architecture, decoration and interior fittings, and objects of everyday usage). An intermediate ‘semi-imaging’ form was, for example, represented with a fabric or scenography. Bogucki defined the realism of a masterpiece as something that reflects reality by the use of means other than an image – it shapes and expresses reality. By avoiding unwanted associations with functionalism or constructivism, he showed ‘realistic’ features of objects and things: perspicuity, simplicity of composition, purposefulness and the appropriate usage of material and tools, breaking away from the pre-war ornamentation and avant-garde restraint of shapes. Masterpieces of ‘formative’ art were to fulfil the postulate of a national form; hence, the inspiration with a native tradition, folk art and handcraft was recommended. Crucial propagandistic slogans concerned popularization and ‘democratization’ of art connected with both creation and reception; industrial production pursuant to the models of professional artists as well as the working class, and folk and teen ‘collectives’ managed by them. Chosen institutions served popularization and democratization of socialist art. The 1952 Exhibition of Interior Architecture and Decorative Art and especially the criticism linked with it, regarding the assumptions of socialist realism and gradual abandoning the criteria of the doctrine from around 1954, are presented in this text. Reckoning with the method: during the public thaw (1956–1957), when categories of realism and national form were replaced with the imperative of modernity, constitutes a recapitulation.